Peran Pesantren Lansia Bagi Perkembangan Pendidikan Islam: Studi Kasus Di Pondok Pesantren Raudlatul Ulum Kencong Kepung Kediri - Khotimah, Husnul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
This study was conducted to examine and describe YayasanPondok Pesantren Raudlatul Ulum Kencong Pare (YPPRUK) which isintended to take care of elderly. There are three aspects to consider amongelderly population. They are biological, economic and social aspects. Byusing qualitative approach in the form of case study, the research revealsthe following findings. Firstly, YPPRUK is a forum for elderly people todeepen their religious knowledge, or so-called facilitators. Secondly, itaims at motivating senior citizens in the village Kencong to raise charitywith emphasis on worship in order to draw closer to Allah SWT. Thirdly,Uswah hasanah as the method employed as the learning strategies isactually a method that has been familiar among schools.Key words: Elderly people, Education, Islam, YPPRUK